Inklusivitas aktor dalam agenda Sustainable Development Goals (SDGs): Peran Pemerintah Provinsi melalui tinjauan Global Governance: THE ROLE OF THE PROVINCIAL GOVERNMENT THROUGH THE GLOBAL GOVERNANCE REVIEW - Akbar, Raden Rahadian Firman; Sari, Deasy Silvya; Rezasyah, Teuku (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2025)
This article discusses the role of the West Java Provincial Government in supporting the achievement of the Sustainable Development Goals (SDGs), as a form of inclusiveness of actors within the framework promoted by this agenda. The issue raised in this study is how subnational actors, particularly provincial governments, can contribute to bridging global interests with local needs, as well as how their institutional capacity influences this process. To answer this question, the study uses a global governance framework to analyse the dynamics of subnational actors' involvement in SDG implementation, examining it through a governance activity matrix. Methodologically, this study employs a qualitative approach with descriptive analysis, drawing on literature studies and reviews of policy documents related to the implementation of the SDGs in West Java. The findings show that through the global governance perspective, subnational actors possess the capacity to actively participate and make significant contributions to achieving the SDGs through policy integration that reflects both global and national sustainability interests, while also being relevant to the local context. However, the dispersed nature of the relationship between levels has created several gaps, particularly in certain SDG goals, reflecting the complexity of coordination and the challenges in implementation.